The Penguin book of infidelities - Brook, Stephen (Viking, 1994)
Here is a glorious assembly of infidelities, ranged under thematic headings that include Cravings, The Spouse's Shadow, Sex: Real and Imagined, Deception and After the Affair. It also offers a procession of historic affairs of the heart - an anatomy of the frailties and adulteries of the great and the good - from the battlements of Troy through the salons of Europe to today's corridors of power.